You are on page 1of 7

# 1

CHAPTER 5
DEFLECTION AND STIFFNESS

Beam deflection can be found by 3 methods: 1) Integration, 2) Superposition and 3)
Castiglianos Theorem. These are detailed as follows:

1) Beam deflection by Integration (Section 5-3, pg. 188 in the textbook):

If the deflection of a beam is mainly due to the bending moment, then the following
formula is applied to find the deflection of the beam:

EI
M
dx
y d
2
2
=

where y is the vertical deflection, x is the horizontal distance, E is the modulus
elasticity and I is the area moment of inertia as before. We also find the slope as:

+ = =
1
c dx
EI
M
dx
dy

where c
1
is a constant found from the end or boundary conditions of the beam.

Example: Find general expressions for the deflection and slope of the following
beam.

y y

a FBD:
w F
F wa a/2
B x x

C

First we draw a FBD for the system to find the reactions, which are found from
Newtons equations as R
A
= F+wa and M
A
= FL+wa
2
/2. We then cut the beam
between A-B and B-C to find the bending moments of M
AB
and M
BC
as:

We sum the moments at the cut sections and let them to be zero to find:

M
AB
= R
A
xwx
2
/2M
A
= wx
2
/2+(F+wa)x (FL+ wa
2
/2) and
2
M
BC
= R
A
xwa(xa/2)M
A
= (F+wa)x wa(xa/2) (FL+ wa /2) = F(xL).
w
w
a
M
BC
y
M
A
M
A
M
AB
y
V
AB
R
A
x
V
BC
R
A
x
A R
A M
A

L

L
2
Deflection and Slope between A-B, i.e. 0 x a:

1
2
2
1
)
2
( ) (
2
1
c dx
a w
FL x wa F x
w
EI
c dx
EI
M
dx
dy
AB
+
(
(

+ + +

= + =

Slope =
AB
=
=
1
2
2 3
)
2
(
2
) ( 1
c x
a w
FL x
wa F
x
w
+
(
(

+
+
+

6 EI

Since
AB
= 0 at x =0 then c
1
= 0. Hence:

AB
=

(
(

+
+
+

x
a w
FL x
wa F
x
w
EI
)
2
(
2
) (
6
1
2
2 3
.

Deflection=y
AB
=
2
2
2 3
2
)
2
(
2
) (
6
1
c dx x
a w
FL x
wa F
x
w
EI
c dx
AB
+
(
(

+
+
+

= +

=
2
2
2
3 4
4
) (2
6
) (
24
1
c x
a w FL
x
wa F
x
w
EI
+
(
(

+
+

Since y
AB
= 0 at x =0 then c
2
= 0. Hence:
y
AB
=

(
(

+
+

2
2
3 4
4
) (2
6
) (
24
1
x
a w FL
x
wa F
x
w
EI
.

eflection and Slope between B-C, i.e. a x L: D
lope =
BC
=

3 3
) (
1
c dx L x F
EI
c dx
EI
M
dx
dy
BC
+ = + =

S
=
3
2
)
2
( c Lx
x F
+
EI
.

ince
AB
=
BC
at x =a where from the above equations: S
a x AB =
=
(
(

+ + a FL a a
EI
)
2
(
2 6
(

)
2
(
6
1
3
L
a
Fa a
w
EI

(
+ a w wa F w ) ( 1
2
2 3
=
a x BC =
=
3
2
)
2
( c La
a
EI
F
+ and hence c
3
=
EI
wa
6
3

. Therefore:

BC
=
(
(

6
)
2
(
1
2 3
wa
Lx
x
F
EI
.

3
Deflection = y
BC
=
4
2
4
6
)
2
(
1
c dx
wa
Lx
x
F
EI
c dx
3
BC
+
(
(

= +

.
=
4
2 3
6
)
2 6
(
1
c x
wa x
L
x
F
EI
3
+
(
(

Since y
AB
= y
BC
at x =a where from the above equations:
a x AB
y
=
=
(
(

+
+

2
2
3 4
4
) (2
6
) (
24
a
a w FL
a
wa F
a
w
EI
1
=
=
(
(

+
2 6 8
2 3 4
FLa Fa
EI

1 wa
.
a x BC
y
=
=
4
2 3
6
)
2 6
(
1
c a
wa a
L
a
F
EI
3
+
(
(

and hence c
4
=
EI
wa
24
4
. Therefore:

y
BC
=
(
(

+
24 6
)
2 6
(
1
4 2 3
wa
x
wa x
L
x
F
EI
3
.

Note: Review example 5-1, pg. 190 in the textbook.

2) Beam Deflection by Superposition (Section 5-5, pg. 192 in the textbook):

Refer to 16 cases given in the Appendix A-9, from pg. 969 to 976 in the textbook. The
superposition for linear systems means that we can find the reactions, bending
moments, shear forces, slope and deflection by summing up these entities for each
loading case. So lets solve the above example by the superposition technique. We
have,
y y
y
a w a w
F
F
B B x
+

C C C A A A L L L

Deflection and Slope between A-B, i.e. 0 x a:

Slope =
AB
=
1AB
+
2AB
, where from Table A-9-3, pg. 970 in the textbook,

1AB
=
dx
dy
= ) x a x ax (
EI
w
2 3 2
3 3
6
where l is replaced by a in the formula. Also,
from Table A-9-1, pg. 969 in the textbook,
2AB
=
dx
dy
= ) Lx x (
EI
F
2
2
2
. Hence,

4

AB
= ) x a x ax (
EI
w
2 3 2
3 3
6
+ ) Lx x (
EI
F
2
2
2
=
(
(

+
+
+

x
a w
FL x
wa F
x
w
EI
)
2
(
2
) (
6
1
2
2 3
,
which is the same result obtained before using the integration method.
Deflection =y
AB
= y
1AB
+ y
2AB
, where from Table A-9-3, pg. 970 in the textbook,
y
1AB
= ) 6 (4
24
2 2
2
a x ax
EI
wx
where again l is replaced by a in the formula. Also,
from Table A-9-1, pg. 969 in the textbook, y
2AB
= ) L x (
EI
Fx
3
6
2
. Hence,

y
AB
= ) 6 (4
24
2 2
2
a x ax
EI
wx
+ ) 3 (
6
2
L x
EI
Fx
=
(
(

+
+

2
2
3 4
4
) (2
6
) (
24
1
x
a w FL
x
wa F
x
w
EI
,
which is again the same result obtained before using the integration method.

Deflection and Slope between A-B, i.e. a x L:

Slope =
BC
=
1BC
+
2BC
. Since there is no bending moment between B-C for the case
of distributed load w, we can assume that the slope remains the same as
1AB
at x=a.
Hence,
1BC
=
a x AB 1 =
=
EI
wa
3
6

## . Also, from Table A-9-1, pg. 969 in the textbook,

2BC
=
2AB
= ) 2 (
2
2
Lx x
EI
F
. Hence,

BC
=
EI
wa
3
6

+ ) 2 (
2
2
Lx x
EI
F
=
(
(

6
)
2
(
1
2 3
wa
Lx
x
F
EI
,
which is the same result obtained before using the integration method.

Deflection =y
BC
= y
1BC
+ y
2BC
.
For the case of distributed load w, the angle
1BC
remains the same between B-C, and
hence the deflected curve between B-C is a linear one.

y
w
a
Deflected Curve
B
C
y
1B
A
y
1BC
x

1BC

From the figure, y
1BC
=
1BC
(xa)+ y
1B
, where y
1B
=
a x AB 1
y
=
=
EI
wa
8
4

. Therefore,
y
1BC
=
EI
a x wa
6
) (
3

+
EI
wa
8
4

= ) 4 (
24
3
a x
EI
wa
+ .
5
For the end load of F, again referring to Table A-9-1, pg. 969 in the textbook, y
2BC
=
y
2AB
= ) 3 (
6
2
L x
EI
Fx
. Hence,

y
BC
= = y
1BC
+ y
2BC
= ) 4 (
24
3
a x
EI
wa
+ + ) L x (
EI
Fx
3
6
2
=
(
(

+
24 6
)
2 6
(
1
4 2 3
wa
x
wa x
L
x
F
EI
3
,
which is again the same result obtained before using the integration method.

Note: Review examples 5-2 and 5-3, pgs. 192 and 193 in the textbook.

3) Beam Deflection by Castiglianos Theorem (Sections 5-7 and 5-8, pgs. 198 and
201 in the textbook):

When a machine element is deformed, it stores a potential or strain energy U. This

Tension or Compression
EA
L F
2
2

Direct Shear
GA
L F
2
2

Torsion
GJ
L T
2
2

Bending Moment

EI
dx M
2
2

Bending Shear

GA
dx cV
2
2

where for bending shear c is a factor that depends on the cross-section of the beam
and is taken from Table 5-1, pg. 200, in the textbook. The Castiglianos theorem then
states that the displacement for any point on a machine element is the partial
derivative of the strain energy with respective to a force which is on the same point
and in the same direction of the displacement. In short:
i
i
F
U

=
where
i
is the displacement for an i
th
point in the machine element and F
i
is the force
acting at the same point and in the same direction of the displacement asked for. If
there is no force at the point for which the displacement is required, then we have to
assume an imaginary force Q and let it be zero at the end.

Example: Lets solve the above problem for its vertical displacement at the free end,
i.e. at point C, using the Castiglianos theorem. So the question is to find
C
in the
vertical (y) direction. We have,

F
U
C

=
6
where the strain energy U is contributed by the bending shear force V and bending
moment M, but well only consider the effect of M in U. Thus, as given above,

U =

EI
dx M
2
2
=

+
L
a
BC
a
AB
EI
dx M
EI
dx M
2 2
2
0
2

and

=
L
a
BC
BC
a
AB
AB
C
EI
dx
F
M
M
EI
dx
F
M
M
0

where as found before: M
AB
= wx
2
/2+(F+wa)x (FL+ wa
2
/2) and M
BC
= F(xL).
Therefore: L x
F
M
AB
=

and L x
F
M
BC
=

## . Substituting these in the formula

above yields:
| |
dx
EI
L x F
dx
EI
L x wa FL x wa F wx
L
a
a
C

+
+ + +
=
2
0
2 2
) ( ) ( /2) ( ) ( /2
.
which upon calculation results in

EI
FL
a L
EI
wa
C
3
) (4
24
3 3
+ = .

This result is in agreement with the result that can be found from the two methods
above by substituting x=L in y
BC
. But remember that
L x BC
y
=
=
C
. Why?

Note: Review examples 5-10, 5-11 and 5-12, pgs. 202 to 206 in the textbook.

5.10 Statically Indeterminate Problems

When a static problem has more unknowns than the Newtons static equations, then
this problem is known as the statically indeterminate problem. In these cases, we need
extra displacement equations to solve the problem. There are two procedures to
handle such problems, among which well follow the Procedure 1 in the textbook,
whose steps are given as follows:

1) Choose the redundant (extra) reaction(s). This redundant reaction could be
a force or a moment.
2) Write the Newtons equations of static equilibrium in terms of the applied
loads and the redundant reaction(s) of step 1.
3) Write the deflection or slope equation(s) for the point(s) of the redundant
reaction(s) of step 1. Normally this deflection or slope will be zero.
4) Solve the equations in steps 2 and 3 for the reactions.

Note: Review example 5-14, pgs. 212 and 213 in the textbook.

7

called buckling, which needs to be checked for the safe use of these columns. Such
columns with 4 different end conditions are shown in the textbook in Figure 5-18, pg.
217. The formula used for the long columns is named Euler formula, given as:

2
cr
L
EI c
P
2

= or
2
2
) / ( k L
E c
A
P
cr

=

where P
cr
is the critical or maximum central load for the column, c is the end
condition constant that should be taken from Table 5-2, pg. 220, in the textbook, and k
is the radius of gyration found from I = Ak
2
, which is equal to d/4 for a column having
a solid round cross-section with a diameter of d. L/k in the formula is known as the
slenderness ratio. There are 2 scenarios here:

1) If the critical load P
cr
is known, then one should use the above equations to
find an adequate cross-section for the column.
2) If the cross-section of the column is known, one can use the above equations
to solve for the P
cr
.

How do we know a column is long enough or it is of intermediate length? First we
define:
1/2
2
1
2
|
|
.
|

\
|
= |
.
|

\
|
y
S
cE
k
L

where S
y
is the yield strength of the column material. We follow the following
criterion:
1) If |
.
|

\
|
k
L
>
1
|
.
|

\
|
k
L
then use the above Euler formula.
2) If |
.
|

\
|
k
L

1
|
.
|

\
|
k
L
then use the Johnson formula given below in section 5-13 for
the intermediate-length columns.

Use the Johnson formula:

cE k
L
S
S
A
P y
y
cr
1
2
2
|
|
.
|

\
|
=

Note: Review examples 5-16, 5-17, 5-18 and 5-19, pgs. 223 to 225 in the textbook.